2016
DOI: 10.1108/ijem-10-2014-0140
|View full text |Cite
|
Sign up to set email alerts
|

Linking teacher competences to organizational citizenship behaviour

Abstract: Purpose – The purpose of this paper is to examine relationship between teacher competences and organizational citizenship behavior (OCB) with empowerment as a mediating factor. Design/methodology/approach – The study took a cross-sectional descriptive and analytical design. Using cluster and random sampling procedures, data were obtained from 383 usable questionnaires. Data were analyzed through SPSS and Analysis of Moment Structures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 32 publications
(35 reference statements)
1
17
1
1
Order By: Relevance
“…Employee competence: There is no single specific scale in the available literature for measuring employees’ competence. Researchers have used different measures in different settings/organizations across the countries to measure the construct (Bjornali & Storen, 2012; Kamukama et al, 2017; Kasekende et al, 2016; Otoo, 2019; Puteh et al, 2016; Urtasun & Nunez, 2012; van Esch et al, 2018). However, there is no consensus regarding the dimensions/items of the scale.…”
Section: Methodsmentioning
confidence: 99%
“…Employee competence: There is no single specific scale in the available literature for measuring employees’ competence. Researchers have used different measures in different settings/organizations across the countries to measure the construct (Bjornali & Storen, 2012; Kamukama et al, 2017; Kasekende et al, 2016; Otoo, 2019; Puteh et al, 2016; Urtasun & Nunez, 2012; van Esch et al, 2018). However, there is no consensus regarding the dimensions/items of the scale.…”
Section: Methodsmentioning
confidence: 99%
“…The psychological contract contains beliefs about the employer's obligations to the employee and the employee's obligations to the employer (Bordia et al 2017;Chen, Tsui & Zhong 2008;Rousseau 1995), which is also referred to as the contents of the psychological contract. Many researchers (Bal, Chiaburu & Jansen 2010;Kasekende et al 2016) have indicated that the perceptions of employers and employees about the fulfilment of their unwritten expectations and obligations are important, since it could result in a perception of psychological contract breach. A breach of the psychological contract can occur when any of the psychological contract obligations were perceived as not delivered (Bordia et al 2017).…”
Section: Obligations Towards and Preemployment Violation Of The Anticipatory Psychological Contractmentioning
confidence: 99%
“…According to the principles of psychological contract theory, the expectations that employees have automatically become the obligation of the employer, and vice versa (Kasekende et al 2016). Kasekende (2017) defines obligations as a promise of future action, which the parties have agreed upon, even though the terms of the promise, the execution thereof and degree of mutuality open the contract to disagreements.…”
Section: Obligations Towards and Preemployment Violation Of The Anticipatory Psychological Contractmentioning
confidence: 99%
“…Empowerment, motivation, and professional growth positively contribute to the productivity of any organization particularly among schools or academic institutions. Leaders should initiate and support for the development of employees or workers as capital of excellence and competitiveness (Kasekende, 2016).…”
Section: Rationalementioning
confidence: 99%